Study on cerebrospinal fluid meropenem, vancomycin and tigecycline monitoring in patients with central nervous system infection following neurosurgery under different drug regimens - Zhao, Xiaoman; Qiao, Yanan; Xie, Qing; Zhang, Zheng; Song, Yan; Kang, Jianbang; Li, Jinchuan; Duan, Jinju (Frontiers in Pharmacology, 2025)
IntroductionCentral nervous system infection (CNSI) following neurosurgery is challenging to treat and carries a high risk of recurrence, morbidity, and mortality. Low CNS penetration of antibiotics may contribute to poor clinical outcomes from CNS infections. Different drug regimens also suggested variable impacts on clinical outcomes. This study aims to measure the cerebrospinal fluid (CSF) concentration of meropenem, vancomycin and tigecycline in patients with CNSI following neurosurgery and thus evaluate the differential therapeutic efficacy of different drug regimens.MethodsPatients who received meropenem, vancomycin and/or tigecycline for highly suspected or confirmed bacterial CNSI following neurosurgery were recruited from a tertiary hospital in Shanxi from January 2021 through December 2022. The concentrations of these three antibiotics in CSF and/or plasma were determined by high-performance liquid chromatography (HPLC) or enzyme immunoassay. Relevant pharmacokinetic/pharmacodynamic (PK/PD) parameters were assessed using DAS 2.0 software. Body temperature, biochemical examination and bacterial culture results were collected to evaluate efficacy.ResultsIn total, 55 CSF and ten plasma samples obtained from ten patients were included in this study. In particular, of five patients who had a positive CSF culture, four achieved culture conversion to negative. Nine individuals successfully achieved CSF, blood tests, or body temperature improvement. Only one patient showed no improvement at discharge.ConclusionThe CSF concentration and PK/PD parameters of meropenem, vancomycin, and tigecycline in patients with CNSI following neurosurgery featured large inter-individual variation. Different drug regimens can partially improved the outcomes of such patients, but monitoring of potential adverse reactions is required.